2012
DOI: 10.1111/hex.12020
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of patient‐centred care: empirical test of a theoretical model

Abstract: Aim Patient perception measures are gaining increasing interest among scholars and practitioners. The aim of this study was to empirically examine a conceptual model of patient-centred care using patient perception survey data.Background Patient-centred care is one of the Institute of Medicine's objectives for improving health care in the 21st century. Patient interviews conducted by the Picker Institute/Commonwealth Fund in the 1980s resulted in a theoretical model and survey questions with dimensions and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 37 publications
3
78
0
Order By: Relevance
“…The change of roles also creates familiarity between the patients and the staff members and creates an intimacy that goes beyond the care itself. Here an example that was observed between a nurse and a patient: "The nurse asks patient 11 if she used to bike. The patient confirms and says that nowadays it is too exhausting, especially with the mountains.…”
Section: C) Change Of Rolesmentioning
confidence: 99%
“…The change of roles also creates familiarity between the patients and the staff members and creates an intimacy that goes beyond the care itself. Here an example that was observed between a nurse and a patient: "The nurse asks patient 11 if she used to bike. The patient confirms and says that nowadays it is too exhausting, especially with the mountains.…”
Section: C) Change Of Rolesmentioning
confidence: 99%
“…Perceived quality of care has been conceptualised as a combination of several dimensions of patient experience, including (1) respect for preferences, (2) care coordination, (3) information, education, and communication, (4) physical comfort, (5) emotional support, (6) involvement of family and friends, and (7) continuity and transition . A US study of patient experiences found emotional support played a key role in determining quality perceptions .…”
Section: Introductionmentioning
confidence: 99%
“…These services aim to provide a treatment environment, emotional support, and care that are tailored to the unique psychosocial needs of this cohort with the expectation that AYAs' care experiences will improve and their unmet needs reduce. These centres also aim to improve the coordination of AYAs' care, which has been shown to play an important role in perceptions of care quality . However, to date, no study has examined whether more positive care experiences (eg, age appropriateness, emotional support, and greater information provision) are associated with reduced needs and consequently better QOL in AYAs.…”
Section: Introductionmentioning
confidence: 99%
“…Responding to the needs and preferences of patients for the delivery of health care is an important aspect of current healthcare policy worldwide . It leads to positive clinical outcomes, for example better survival or physical and emotional recovery, and increased patient satisfaction . Increased patient satisfaction might result in a better adherence to treatment recommendations and increase quality of life …”
Section: Introductionmentioning
confidence: 99%